2018
DOI: 10.1096/fj.201801198r
|View full text |Cite
|
Sign up to set email alerts
|

MPB, a novel berberine derivative, enhances lysosomal and bactericidal properties via TGF‐β–activated kinase 1‐dependent activation of the transcription factor EB

Abstract: Lysosome has a crucial role in clearance of endocytosed pathogens from the cell. Small molecules that can boost lysosome function and bactericidal ability to cope with subsequent infection are urgently needed. Here, we report that MPB, a novel berberine derivative, induced lysosome-based degradation and clearance of methicillin-resistant Staphylococcus aureus and enteroinvasive Escherichia coli in macrophages. MPB caused nuclear translocation of transcription factor EB (TFEB), which boosted expression of lysos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 59 publications
(79 reference statements)
0
9
0
Order By: Relevance
“…Further, genetic or chemical modulation of the host lysosomes correspondingly affected the intracellular survival of Salmonella suggesting that the intracellular growth of Salmonella is affected by the lysosomes (McGourty et al, 2012). Several other studies have also reported that the chemical or genetic enrichment of lysosomes enhances bactericidal properties and bacterial clearance of other pathogens such as Burkholderia cenocepacia, methicillin-resistant Staphylococcus aureus and enteroinvasive Escherichia coli (Sogi et al, 2017;Vural et al, 2018;Liu et al, 2019). These studies show an emerging consensus with these limited examples of the global content of lysosomes in cells having a growth inhibitory effect on intracellular pathogens.…”
Section: Role Of the Global Lysosomal Alterations In Pathogenesis Mecmentioning
confidence: 99%
“…Further, genetic or chemical modulation of the host lysosomes correspondingly affected the intracellular survival of Salmonella suggesting that the intracellular growth of Salmonella is affected by the lysosomes (McGourty et al, 2012). Several other studies have also reported that the chemical or genetic enrichment of lysosomes enhances bactericidal properties and bacterial clearance of other pathogens such as Burkholderia cenocepacia, methicillin-resistant Staphylococcus aureus and enteroinvasive Escherichia coli (Sogi et al, 2017;Vural et al, 2018;Liu et al, 2019). These studies show an emerging consensus with these limited examples of the global content of lysosomes in cells having a growth inhibitory effect on intracellular pathogens.…”
Section: Role Of the Global Lysosomal Alterations In Pathogenesis Mecmentioning
confidence: 99%
“…TFEB is involved in host response by regulating both innate and adaptive immunity ( Brady et al, 2018b ; Irazoqui, 2020 ). It has been documented that TFEB participates in the process of macrophage activation by following mechanisms ( Fang L. et al, 2017 ), including promoting bactericidal function ( Gray et al, 2016 ; Liu X. et al, 2019 ) and facilitating the production of various proinflammatory mediators ( Visvikis et al, 2014 ; Pastore et al, 2016 ; Figure 2Ca ). TFEB is demonstrated to play a role in innate immune response by modulating xenophagy, a form of selective autophagy targeting invaded microorganisms ( Wang and Li, 2020 ).…”
Section: The Function Of Tfebmentioning
confidence: 99%
“…The referred study revealed a novel mechanism by which MPB controls jun N-terminal kinase (JNK) and AMP-activated protein kinase (AMPK) phosphorylation cascades to activate lysosomal function and bactericidal activity via TAK1 K158-dependent manner, which may offer insight into novel therapeutic strategies to control bacterial infection. 118 In the last few years, there has been extensive progress on understanding autophagy regulators from natural products, which provide new insights into the development of treatment strategies for AD by targeting autophagy in animal models. In the present review, we provide an overview of current research assessing the role of autophagy in AD, including the regulation mechanisms of ALP and the therapeutic potential of herbal medicine in AD by targeting autophagy.…”
Section: Berberinementioning
confidence: 99%
“…Recently, researchers have shown thatMPB, a novel berberine derivative, induced lysosome‐based degradation and clearance of methicillin‐resistant Staphylococcus aureus and Escherichia coli in macrophages. The referred study revealed a novel mechanism by which MPB controls jun N‐terminal kinase (JNK) and AMP‐activated protein kinase (AMPK) phosphorylation cascades to activate lysosomal function and bactericidal activity via TAK1 K158‐dependent manner, which may offer insight into novel therapeutic strategies to control bacterial infection 118 . In the last few years, there has been extensive progress on understanding autophagy regulators from natural products, which provide new insights into the development of treatment strategies for AD by targeting autophagy in animal models.…”
Section: The Role Of Phytochemicals In the Treatment Of Admentioning
confidence: 99%